Maternal Vitamin B12 in Pregnancy and Placental Development - Amrita Arcot; Rachel E. Walker; Kelly Gallagher; Kevin C. Klatt; Alison D. Gernand (Journal of Nutrition and Metabolism)
Vitamin B12, or cobalamin, is an essential nutrient required for diverse physiological functions secondary to its role as a critical cofactor for two mammalian enzymes, methionine synthase and methylmalonyl-CoA mutase. While essential throughout all life stages, several pathways that require vitamin B12, including hematopoiesis, myelination, and DNA/histone methylation, are particularly critical during pregnancy and fetal development. This narrative review aims to describe vitamin B12 in pregnancy, with emphasis on the placenta’s role in ensuring adequate nutrition of the fetus and impacts of vitamin B12 deficiency on placental development and function. Our literature search included preclinical model systems and human cohorts and interventions. Our review identified evidence of B12 deficiency resulting in impaired placental development, greater placental inflammation, and modulation of placental docosahexaenoic acid concentration, collectively suggestive of vitamin B12 deficiency as a determinant of both maternal and fetal health outcomes. Heterogeneity in study design complicated generalization of findings. Future studies should consider selecting a B12 marker that is relatively stable across pregnancy, such as holotranscobalamin, while accounting for important confounders such as maternal folate.